Protective effects of resveratrol on the expression of catalase, glutathione peroxidase, and superoxide dismutase genes in the ovary and their activity in the serum of rats exposed to lead acetate: An experimental study - Mohammad Karimian; Mozhdeh Ghadiri; Seyedeh Mahsa Poormoosavi; Hossein Najafzadehvarzi (International Journal of Reproductive BioMedicine)
Background: Lead (Pb) could be toxic to the female reproductive system, and resveratrol (Res) may overcome this toxicity.